Ways to improve the effectiveness of glaucoma filtering surgery - V. P. Nikolaenko; A. V. Antonova; V. V. Brzhesky (Российский офтальмологический журнал)
The article presents a variety of ways to increase the efficiency of glaucoma filtering surgery. Special attention is given to maintaining the ocular surface healthy through optimal glaucoma therapy. The duration of the disease should be taken into account when choosing the type of hypotensive surgery and designing an algorithm for its pharmacological support: preoperative preparation, prolonged postoperative anti-inflammatory treatment and cornea protection.